2003
DOI: 10.1074/jbc.m309377200
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Hepatic Triglyceride Accumulation and Altered Fatty Acid Uptake in Mice with Deletion of the Liver Fatty Acid-binding Protein Gene

Abstract: Liver fatty acid-binding protein (L-Fabp

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
286
5
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(319 citation statements)
references
References 31 publications
24
286
5
4
Order By: Relevance
“…SCP2 is thought to be present in sufficiently close enough proximity for direct interaction with SR-BI (10) and our earlier results have demonstrated the interaction as well as hydrolysis of SR-BI-delivered HDL-CE by CEH (3). Consistently, SCP2 deficiency failed to increase CEH-mediated hydrolysis of HDL-CE and overexpression of SCP2 in SR-BI / mice also failed to increase hydrolysis is consistent with earlier studies demonstrating SCP2-mediated increase in CYP7A1 activity and bile acid synthesis in vitro (24). SCP2 is also thought to be involved in transport of FC to the endoplasmic reticulum and it is highly likely that by making FC available at the endoplasmic reticulum, SCP2 also increases CYP7A1 activity in vivo and stimulates bile acid synthesis.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…SCP2 is thought to be present in sufficiently close enough proximity for direct interaction with SR-BI (10) and our earlier results have demonstrated the interaction as well as hydrolysis of SR-BI-delivered HDL-CE by CEH (3). Consistently, SCP2 deficiency failed to increase CEH-mediated hydrolysis of HDL-CE and overexpression of SCP2 in SR-BI / mice also failed to increase hydrolysis is consistent with earlier studies demonstrating SCP2-mediated increase in CYP7A1 activity and bile acid synthesis in vitro (24). SCP2 is also thought to be involved in transport of FC to the endoplasmic reticulum and it is highly likely that by making FC available at the endoplasmic reticulum, SCP2 also increases CYP7A1 activity in vivo and stimulates bile acid synthesis.…”
Section: Discussionsupporting
confidence: 73%
“…The importance of defining the role of SCP2 or FABP1 in regulating the flux of HDL-CE is underscored by the fact that human genetic variations in SCP2 inhibit cholesterol metabolism (20), a phenotype shared with SCP2 / mice (21) and human liver fatty acid binding protein (L-FABP) T94A polymorphism that occurs with a frequency of 32-37% in Caucasians results in hepatic cholesterol accumulation (22). It is noteworthy that deficiency of either SCP2 or FABP1 does not affect the levels of plasma triglyceride, cholesterol, or nonesterified fatty acids in mice (21,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse, targeted deletion of the L-FABP gene resulted in a reduced rate of LCFA uptake by the liver under conditions of high lipid supply (e.g. intravenous LCFA bolus or prolonged fasting) (18,19). Fasted L-FABP-null mice were characterized by lower hepatic TG synthesis and fatty acid oxidation than wild-type controls (19,20).…”
mentioning
confidence: 99%
“…The rate of cytoplasmatic transport of FFA is proportional to the concentration of FABP in the liver (Weisiger, 2002), and inhibition of FABP reduces intracellular FFA transport (Luxon, 1996). Studies with FABP -/-mice showed that these mice exhibited diminished hepatic β-oxidation that was not caused by an impaired oxidative capacity (Atshaves et al, 2010,Newberry et al, 2003. This result lead to the hypothesis, that hepatic FABP acts as a transporter of FFA to the site of β-oxidation (Storch and Thumser, 2010).…”
Section: Iii52 Fatty Acid (Fa) Import and Transportmentioning
confidence: 86%
“…This result lead to the hypothesis, that hepatic FABP acts as a transporter of FFA to the site of β-oxidation (Storch and Thumser, 2010). Additionally, FABP deficient mice show reduced FA uptake and decreased hepatic TG levels when fed a HFD (Newberry et al, 2003,Newberry et al, 2006. The hepatic isoform is FABP1, and qPCR revealed that the expression of this carrier protein was significantly elevated in PI3K p110γ deficient mice fed HFD but not in WT mice on the same diet (Fig 29).…”
Section: Iii52 Fatty Acid (Fa) Import and Transportmentioning
confidence: 92%